Nilai Lokal dalam Perencanaan Tata Ruang Kota Muntilan - Shawma, Nadia Gita; Setyono, Jawoto Sih (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2014)
Muntilan is one of a small city that cities that respond to the development and modernization . In addition to its position on the national path that connects Yogyakarta to Semarang as the capital of the each province, in a fact Muntilan was probably save any locality aspects such as natural conditions, as the descendants of Javanese society and diversity religious that exists but at the same time they are become the opportunity for the development of Muntilan. These phenomena will be continue to emerge thatÂ  influence in the direction of urban space which is arranged by the government in a process and a product of spatial planning. The research about local values in spatial planning use The Grounded Theory approach was successfully finds local values that formed from the interaction of society with the aspects of localities , including community perceptions for the threat of Merapi Mountain , their love as Javanese, the faith value that hidden on stone carving art, mina lumping art, and tolerance and harmony among diverences of religions in Muntilanâ€™s society. There is the only one of the local value that considered in spatial planning and contained within the spatial planning documents, RDTRK Muntilan. The others local values that has not regulated by local government in spatial planning, serve as recommendations to the government and stakeholders to make the implementation of spatial planning for the small town of Muntilan.